Effects of Mindfulness Training on Sleep Problems in Patients With Fibromyalgia - Amutio, Alberto; Franco, Clemente; Sánchez-Sánchez, Laura C.; Pérez-Fuentes, María del C.; Gázquez-Linares, José J.; Van Gordon, William; Molero-Jurado, María del M. (Frontiers in Psychology, 2018)
Fibromyalgia syndrome (FMS) is a complex psychosomatic pain condition. In addition to generalized pain and various cognitive difficulties, new FMS diagnostic criteria acknowledge fatigue and sleep problems as core aspects of this condition. Indeed, poor sleep quality has been found to be a significant predictor of pain, fatigue and maladaptive social functioning in this patient group. While there is promising evidence supporting the role of mindfulness as a treatment for FMS, to date, mindfulness intervention studies have principally focused on dimensions of pain as the primary outcome with sleep problems either not being assessed or included as a secondary consideration. Given the role of sleep problems in the pathogenesis of FMS, and given that mindfulness has been shown to improve sleep problems in other clinical conditions, the present study explored the effects of a mindfulness-based intervention known as Flow Meditation (Meditación-Fluir) on a range of sleep-related outcomes (subjective insomnia, sleep quality, sleepiness and sleep impairment) in individuals with FMS. Adult women with FMS (n = 39) were randomly assigned to the seven-week mindfulness treatment or a waiting list control group. Results showed that compared to the control group, individuals in the mindfulness group demonstrated significant improvements across all outcome measures and that the intervention effects were maintained at a three-month follow-up assessment. The Meditación-Fluir program shows promise for alleviating sleep problems relating to FMS and may thus have a role in the treatment of FMS as well as other pain disorders in which sleep impairment is a central feature of the condition.